Impedance measurements on the passive layers of stainless different heat treated steels - Slemnik, Mojca (Acta chimica slovenica, 2002)
The behavior of differently heat-treated X20Cr13 steels in 0.1 M H2SO4, was studied using the electrochemical impedance spectroscopy. Impedance spectra were recorded at constant passsive potentials of 0.2, 0.4 and 0.6 V vs. SCE, respectively. At low passive potential, 0.2 V vs. SCE, impedance spectra typical for an active - passive transition were observed. The assumption has been made, that they are the result of the adsorption process, caused by boundwater, which blocks the passive layer of steel and leads to corrosion rate reduction. The process is the most significant at the oil and the air-quenched, but less at the tempered steel. When more noble potentials are approached the impedance spectra become typical for passive metals and the value of resistance and capacitance differ from each other with respect to the heat treatment.
Keywords: impedanca; korozija; nerjavna jekla